Integrale Brücken : Entwurf, Berechnung, Ausführung, Monitoring /: Entwurf, Berechnung, Ausführung, Monitoring. ([2017]) - Geier, Roman; Angelmaier, Volkhard; Graubner, Carl-Alexander; Kohoutek, Jaroslav
No abstract available